The diagnostic value of cardiac magnetic resonance in athletes with suspected structural myocardial diseases. (25th November 2020) - Vago, H; Szabo, L; Balla, D; Dohy, Z.S; Czimbalmos, C.S; Suhai, F.I; Toth, A; Sydo, N; Kiss, O; Vencel, J; Becker, D; Merkely, B
Abstract: Introduction: Sudden cardiac death (SCD) is the leading cause of death in athletes occurring usually during intensive training. Cardiac magnetic resonance (CMR) is a reliable technique to assess ventricular volumes and function. Furthermore, it provides tissue-specific information and has a crucial role in detecting structural myocardial diseases. Aim: We aimed to investigate the prevalence of myocardial structural heart diseases and the etiology of sudden cardiac death in highly trained athletes and their outcome during follow-up. Method: We examined athletes (training ≥6 hours/week) who underwent CMR due to suspected structural myocardial disease at Semmelweis University Heart and Vascular Center between 2009 and 2019. Cine movie images and late gadolinium enhanced (LGE) images were performed. Athletes with structural myocardial alterations were followed for the endpoint of all-cause-mortality. Results: CMR was performed on a total of 338 athletes (280 male, 24±11 age). The indications for CMR were as follows: aborted sudden cardiac death/sustained ventricular tachycardia (SVT) (4%), ECG alterations (36%), echocardiographic alterations (32%), positive family history of SCD or cardiomyopathies (CMP) (3%), and patients' complaints, e.g. palpitation, syncope, dyspnoea, chest complaints (25%). CMR confirmed structural myocardial disease in 82 athletes with the following distribution: 20 hypertrophic (HCM), 10 arrhythmogenic (AC), 8 dilated (DCM), and 7 non-compact (NCCMP) CMP. The CMR images of three patients indicated Fabry disease. We found post-myocardial infarction scars in 7 cases, and atypical non-ischemic scars in 28 athletes. Besides pathological conditions, we identified minor alterations in 58 patients (51 male, 25±12 age) such as: increased trabeculation, nonspecific LGE in left ventricular insertion point and myocardial crypts. Among athletes examined after aborted sudden cardiac death or SVT we found structural heart disease in 11 males and one female: AC (n=7), HCM (n=1), NCCMP (n=1) and atypical non-ischemic scars (n=3, in two patients the localisation was lateral subepicardial) were diagnosed. During the median follow up of five years one patient died in whom CMR showed lateral scar formation and only mildly reduced left ventricular ejection fraction (50%). Conclusions: The most common structural alteration was non-ischaemic scar, the most common CMP was HCM, and the leading cause of sudden cardiac death or SVT in our competitive athletes was AC and lateral subepicardial scar formation. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Project no. NVKP_16-1-2016-0017 has been implemented with the support provided from the National Research, Development and Innovation Fund of Hungary, financed under the NVKP_16 funding scheme. This project was supported by a grant from the National Research, Development and Innovation Office (NKFIH) of Hungary (K 120277).